Exploring heating performance of gas engine heat pump with heat recovery - Dong, Fu-jiang; Liu, Feng-guo; Li, Xian-ting; You, Xue-yi; Zhao, Dong-fang (Journal of Central South University, 2016)
In order to evaluate the heating performance of gas engine heat pump (GEHP) for air-conditioning and hot water supply, a test facility was developed and experiments were performed over a wide range of engine speed (1400-2600 r/min), ambient air temperature (2.4-17.8 °C) and condenser water inlet temperature (30-50 °C). The results show that as engine speed increases from 1400 r/min to 2600 r/min, the total heating capacity and energy consumption increase by about 30% and 89%, respectively; while the heat pump coefficient of performance (COP) and system primary energy ratio (PER) decrease by 44% and 31%, respectively. With the increase of ambient air temperature from 2.4 °C to 17.8 °C, the heat pump COP and system PER increase by 32% and 19%, respectively. Moreover, the heat pump COP and system PER decrease by 27% and 15%, respectively, when the condenser water inlet temperature changes from 30 °C to 50 °C. So, it is obvious that the effect of engine speed on the performance is more significant than the effects of ambient air temperature and condenser water inlet temperature.